Circulating miR-3656 induces human umbilical vein endothelial cell injury by targeting eNOS and ADAMTS13: a novel biomarker for hypertension. Issue 2 (1st February 2022) - Shi, Jikang; Ren, Yaxuan; Liu, Sainan; Zhao, Qian; Kong, Fei; Guo, Yanbo; Xu, Jiayi; Liu, Siyu; Qiao, Yichun; Li, Yong; Liu, Yunkai; Liu, Yawen; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Background: Hypertension, as one of the most common chronic diseases, is a major public health issue. Previous studies have shown that there are miRNAs differentially expressed in hypertensive patients. In addition, hypertension is closely related to endothelial dysfunction, and miRNAs have been identified as important molecular mediators for endothelial function. Therefore, it is necessary to identify specific miRNAs related to hypertension and explore their molecular mechanism in the progression of hypertension. Methods: We investigated the association of circulating levels of miR-3656 with hypertension. Furthermore, in-vitro studies were performed to investigate its possible mechanisms for hypertension in that the direct target genes of miR-3656 were confirmed using dual-luciferase reporter assay; moreover, the effects of miR-3656 on proliferation, migration, apoptosis, and microvascular rarefaction of HUVECs were investigated using MTS kit, wound-healing assay, FITC Annexin V apoptosis detection kit, and tube formation assay, correspondingly. Results: Circulating miR-3656 was upregulated in patients with hypertension. MiR-3656 suppressed the proliferation, migration, and angiogenesis of HUVECs, but promoted the apoptosis of HUVECs. In addition, eNOS and ADAMTS13 were direct target genes of miR-3656, and overexpression of eNOS and ADAMTS13 abolished the effect of miR-3656 on HUVECs. Conclusion: MiR-3656 is a potential biomarker for hypertension. MiR-3656 is involved in endothelial cellular injury implicated in hypertension by targeting eNOS and ADAMTS13 .